Analysis of Communication Pattern as a Social Conflict Solution of Farm Worker Society in the Majalengka Regency - M. Ali Syamsuddin Amin (International Journal of Advanced Science and Technology, 2020)
Communication is essential in social life. Although communication often leads to social conflict, however the solution is resolved through communication too. The lack of communication between farm workers in earning a living often cause of conflict between them. It needs dominant element in order to communication can achieve harmony in competition for income. The purpose of examining three problems is expected to find information can be used to predict the effect of communication that will be done when communicating in various fields of life, both locally and globally. This study uses qualitative with descriptive methods in finding out the quality communication of farm workers from their behavior, and it is supported through literature study from various writings such as books, articles, and other scientific writings, obtaining various information about analytical materials and solutions from the conflict social and also the dominant element needed in the conversation. Communication is widely based on the ambition of individuals and groups can foster various biases, inconsistent character causes misunderstanding, misinterpretation and miscommunication. Inconsistency causes social conflict both horizontally and vertically. Consistent communication on the values of togetherness fosters peace and at the same time becomes a solution for social conflict. The dominant element needed is consistency of the togetherness values yield in mutual understanding. Keywords: Communication, social conflict, consistency, peace.